Can We All Speak the Same 'Language' for Our Patients' Sake? Feedback on Interprofessional Communication and Related Resources - Janet Nguyen; Jennifer Hunter; Lorraine Smith; Amy Forth; Amy Tyler; Louise Furney; Carolyn Ee; Joanna E Harnett (SAGE Publishing, 2021)
Background The Australasian Integrative Medicine Association (AIMA) established a working group to develop the AIMA Guiding Principles for Letter Writing and Letter Writing Templates. The guiding principles were developed to promote effective communication between the diverse range of healthcare practitioners (HCPs) that patients choose to consult. Following the development of the Interprofessional Communication (IPC) resources, AIMA undertook a public consultation as part of a quality assurance process to evaluate the relevance and utility of the resource. Aim This study reports stakeholder feedback on AIMA's draft guiding principles document. It explores stakeholder attitudes towards IPC and HCPs letter-writing, and interest in ongoing continuing professional development (CPD). Methods A cross-sectional survey involving 1) an online public consultation survey and 2) a paper survey collected following IPC CPD activities. Quantitative data were analysed using Chi square and Fisher-Freeman-Halton Test. Responses to open ended questions were coded and subject to a thematic analysis. Results The 64 survey participants and 55 CPD participants represented the Australian healthcare sectors and lay community. Most thought IPC is important (n = 112/117; 96%) and the resources were informative (n = 112/119; 94%), understandable (n = 111/119; 93%), and clinically relevant (n = 105/117; 90%). HCP reported wide variations in their frequency of correspondence with other practitioner types, with rates often concerningly low. Key IPC themes identified were the importance of continuity of care, clarity of communication, and professional practice. CPD participants were most interested in further IPC training (p = 0.001). Conclusions The IPC resources affirm the role of formal communication pathways, such as letters of correspondence to support coordinated, patient-centred and multidisciplinary care. Challenges with letter writing and IPC signal the need for more student and professional education on the subject to promote continuity of patient care and the delivery of high quality, integrative medicine and health care services.